Analysis of Influencing Factors Decision on Interest in Selling Organic Fertilizer By Farm Shops In Gorontalo - Slamet Hasan; Agustinus Moonti; Lusiana (Majapahit Journal of Islamic Finance and Management, 2026)
The agricultural sector plays an important role in supporting economic growth and national food security. However, intensive agricultural practices that rely on chemical fertilizers have had a negative impact on the environment, soil quality, and the availability of production facilities. Organic fertilizers are a more environmentally friendly and sustainable alternative, although the level of use in Gorontalo City is still low. This condition is suspected to be influenced by the low interest of farmer shops as the main actor in the distribution of agricultural inputs. This study aims to analyze the contribution of market potential in encouraging the desire of business actors to market organic fertilizers, examine the extent to which perceptions and obstacles affect the interest in selling organic fertilizers and determine the most influential factors between the perception of barriers and market potential to the interest in selling organic fertilizers, as well as formulate strategic recommendations for the development of sustainable organic fertilizer agribusiness in the Gorontalo area. The research was conducted from August-December 2025 using a quantitative approach through a survey of farmer shop owners. The data was then collected and analyzed using the application of the Statistical Package For The Social Sciences, (SPSS). The results of the study showed that the perception variable was the most powerful variable that had a significant influence on the interest in selling organic fertilizer in Gorontalo City, while other variables also had a significant effect but not yet strong on the interest in selling organic fertilizers.